(untitled) (Journal of Computational Mathematics, 2000)
In this paper, a Kantorovitch-Ostrowski type convergence theorem and an error estimate of \|f'(z_0)^-1f(x_n+1)\|\|f'(z_0)^-1f(x_n)\| using the information of higher derivatives at the center between initial points for King-Werner iteration method in Banach space are established.